Refinement of the Co-Content function, through an integration of a polynomial fit of $$I-I_{sc}$$ I - I sc . Part 2 application to experimental current–voltage curves - Victor-Tapio Rangel-Kuoppa (Discover Electronics)
Abstract In this article Part 2 of this series of articles, the methodology proposed in Part 1, namely, the fitting to a polynomial of the current minus the short-circuit current, i.e., $$I-I_{sc}$$ I - I sc , to calculate the Co-Content function $$\left(CC\left(V,I\right)\right)$$ C C V , I and extract the five solar cell parameters, i.e., the shunt resistance $$\left(R_{sh}\right)$$ R sh , the series resistance $$\left(R_{s}\right)$$ R s , the ideality factor $$\left(n\right)$$ n , the light current $$\left(I_{lig}\right)$$ I lig , and the saturation current $$\left(I_{sat}\right)$$ I sat , (within the one-diode solar cell model), is implemented on reported Current–Voltage (IV) curves found in the literature, both for laboratory made solar cells, as for and single-crystalline silicon (x-Si), multi-crystalline silicon (m-Si), cadmium telluride (CdTe), copper indium gallium selenide (CIGS), amorphous silicon (a-Si) tandem and triple-junction, amorphous silicon/crystalline silicon, heterojunction with intrinsic thin-layer (HIT), and amorphous silicon/microcrystalline silicon photovoltaic modules.